Efectos en la adquisición y transferencia de discriminaciones condicionales de segundo orden debidos a variaciones en las relaciones entrenadas (2005)
The present study explored the effects in acquisition and transference of conditional discriminations, due to the different combinations of the trained relations (identity, difference and similarity) using a second order matching to sample task. In a complementary manner, the experimental task for all the participants comprised characteristics identified in previous studies with a facilitating effective performance effect (like unspecific instructions, stimuli arrangements conformed by 3 shapes and 2 colors and a concurrent training of the relations). 8 subjects were distributed in 4 groups which varied in the combinations of the trained relations. Results showed that almost all of the participants reached the effectiveness criteria during training and extramodal and extrarelational transference tests. All the subjects showed a perfect performance with regard to the identity relation, even when this relation was not trained before. Results are discussed in terms of the effective adjusting velocity to the relations implied, and in accordance to the configurations of the task that seemed to facilitate better performances. Finally, a set of different proposed investigations are discussed, the idea is to overcome the methodological limitations of the present research and to explore possible interactions of the manipulated variables with other important factors. Index terms: second order matching to sample task, transference tests, identity, similarity and difference relations, parametric factors.